Effect of chemical treatment on impact strength and dynamic thermal properties of Jute/PLA composites. (2021) - Manral, Ankit; Kumar Bajpai, Pramendra
Abstract: The Untreated jute fiber reinforced composite (UTJFRC) and treated jute fiber reinforced composite (TJFRC) have been fabricated using compression molding processes. For chemical treatment of jute fiber mat sodium bicarbonate (NaHCO3 ) is used. The solution used for treatment has maintained pH of range 7–8 which show the ecofriendly treatment nature of sodium bicarbonate. Jute fiber mats were treated at three different concentration of sodium bicarbonate at 10, 20 and 30% for 4 h of treatment time. The prepared sample were characterized by dynamic mechanical thermal analysis (DMTA) and Izod impact test. All sample were cut according to ASTM standard to measure izod impact strength on impact tester. The composite sample which were treated at 10% concentration appear high impact strength. Even for dynamic mechanical properties treated jute fiber mat 20% concentration achieved maximum storage and loss modulus values. Even the glass transition temperature (Tg) is maximum shift for 20% concentration treated sample of jute/PLA composites. The improvement in properties because of good interfacial adhesion of jute and PLA achieved by sodium bicarbonate treatment of natural fiber.